Systematic, Pretransplant Screening by Aortoiliac CT Angiography: Impact on Surgical Decision-making and Clinical Outcomes - Marie B. Nielsen, MD, PhD; Jacob Budtz-Lilly, MD, PhD; Jonathan N. Dahl, MD; Anna K. Keller, MD, PhD; Bente Jespersen, MD, DMSc; Per R. Ivarsen, MD, PhD; Simon Winther, MD, DMSc; Henrik Birn, MD, DMSc (Transplantation Direct)
Background. Aortoiliac screening before kidney transplantation is suggested by some guidelines to select patients for transplantation and to assist surgical planning. We investigated the clinical outcomes of systematic screening for aortoiliac disease in potential kidney transplant candidates. Methods. In this observational study, 470 potential kidney transplant candidates underwent aortoiliac computed tomography angiography. Patients were characterized by the presence of peripheral artery disease and calcification of iliac arteries and aortoiliac arteries. The risk of graft loss and graft function at 1 y posttransplant were examined and clinical decisions based on the vascular findings were assessed. Results. Clinically diagnosed peripheral artery disease was present in 66 patients (14%), circular calcifications in 101 patients (21%), and aortoiliac stenosis in 77 patients (16%). In 326 patients undergoing kidney transplantation, circular calcification or aortoiliac stenosis was not associated with an increased risk of graft loss (P = 0.45 and P = 0.28) or estimated glomerular filtration rate (P = 0.23 and P = 0.76) at 1 y posttransplant. When evaluated for transplantability, clinical decision-making based on vascular findings was recorded in 67 of 429 patients (16%), including rejection for transplantation in 7 patients (2%) and laterality for surgical implantation in 52 patients (12%). Conclusions. Systematic screening by aortoiliac computed tomography angiography may assist in surgical planning but seems of limited clinical value in assessing the risk of future graft loss and graft function in patients undergoing kidney transplantation.